Braver Canada : shaping our destiny in a precarious world - Burney, Derek H. (Derek Hudson), 1939-; Hampson, Fen Osler (McGill-Queen's/Brian Mulroney Institute of Government studies in leadership, public policy, and governance, 2020)
"The world is changing--geopolitically and economically--at an alarming fast pace. Populism, protectionism, and authoritarianism are on the rise. Braver Canada analyzes these and many other global shifts, offering provocative prescriptions for both the public and the private sectors. Reviewing the foreign policy challenges, achievements, and missteps of the Justin Trudeau government, Derek Burney and Fen Hampson argue that the country's leadership must craft a new approach to global affairs based on a solid grasp of current and emerging global political and economic realities. They focus on competitiveness, trade, energy, environment, and immigration and refugee issues, also discussing a recalibration of relations with China and India. Expanding on the ideas and policy recommendations in their previous book, Brave New Canada, which called for Canada to diversify its economic ties outside the United States, they note how the global and regional environment has shifted dramatically in recent years. A timely and compelling analysis, Braver Canada lays out the challenges for Canada in a rapidly changing, turbulent world and the strategies required for future prosperity."--